PAIKEM'S APPROACH IN IMPROVING THE LEARNING ACHIEVEMENT OF ISLAMIC RELIGIOUS EDUCATION IN STUDENTS AT STATE ELEMENTARY SCHOOLS INPRES 3 TATURA - Nurafni Idris; Naima Naima; Anisa Anisa (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2025)
This article discuusses the impementation of the PAIKEM approach at SDN Inpres 3 Tatura. The probem raised in this research is what is the process of impementing the PAIKEM approach in improving the earning achievement of Islamic reigious education among student at SDN Inpres 3 Tatura, and what are the obstaces and soutions in inmpeementing the PAIKEM approach in improving the earning achievement of Islamic reigious education among students at SDN Inpres 3 Tatura. The research method in this thesis is quaitative research using a quaitative descriptive approach. This research uses data coection techniques trough, observation, then conducting interviews, and documentation which is amayzed using data reduction, data presentation and data verivication method. The resuts of this research show that the process of impementing an active, innovative, environmenta, creative, effective and interesting earning approach (PAIKEM) has basiccay been used by islamic reigious education teachers at SDN Inpres 3 Tatura. It can be seen from the earning steps used, namey:preparation, earning, activities, refection and discussion, evaotion, and reinforcement and reciprocity. In teaching activities combined with various teaching methods and media so that earning achieviement is achieved we. However, there are sti obstaces encountered when impementing the PAIKEM approach in earning Islamic reigious education are: quaity of teaching staff, readiness of students in receiving essons, teachers who are not optima in using the PAIKEM approach, ack of integrated vision and mission of parents and schoos, passive students. For every obstace that occurs in impamenting the PAIKEM approach, of course there is a soution that must be impemented by Islamic reigious education teachers, namey: a teacher must abe to refect and organize essons we, make the earning process fun and interesting, professiona training and deveopment, good communication reationships between the students parents and the schoo, and must be abe to know more about the students. The impication of the resuts of this research is that teachers can maximize the impementation of the PAIKEM approach so that students are not passive during earning activitie. Apart from that, it can be a consideration for teachers in improving earning achievement and optimizing earning.